Effect of Fish Oil on The Serum Urea Level in Gentamicin Induced Nephrotoxicity in Long Evans Rats - Ahmed, Md Shameem; Yasmin, Ayesha; Ahmed, Md Ashraf; Ashrafuzzaman, -; Mustafa, Rashed; Matin, Md Abdul; Khatun, Margina (KYAMC Journal, 2020)
Background: Gentamicin is used worldwide as bactericidal agent against severe gram negative infections. Gentamicin induced nephrotoxicity can be minimized by administration dietary fish oil. Objectives: The present study was designed to observe the possible potential effect of Fish oil on gentamicin-induced nephrotoxicity in Long Evans rats. Materials and Methods: The experimental study was carried out in the department of anatomy at Dhaka Medical College (DMC) among 40 Long Evans rats of both sex with the weight ranges from 172-255 gm and the age ranges from 7 to 10 weeks. The rats were divided into four groups-Group A (normal control) received normal saline, group B, C and D received gentamicin for 6 days. Rats of group C received fish oil capsule for 9 days with gentamicin and group D received fish oil capsule with gentamicin for total 10 days. Serum urea level was measured at the end of experiment. Results: The serum urea (mean±SD) levels in group A, B, C and D was 4.79±0.32, 12.41±1.22, 6.95±0.91 and 6.18±1.00, respectively. The gentamicin treated rats (group B) had shown increased serum urea levels in comparison to fish oil (group C&D) treated rats. The difference between groups were highly significant (P<0.001) for group A&B, A&C, B&C and B&D. The difference between groups A&D (P<0.01) were moderately significant. Whereas the difference between C&D (P>0.05) was not significant. Conclusion: Fish oil treatment showed some protective effects against gentamicin induced nephrotoxicity. The results also indicated that effectiveness of fish oil depends on a suitable duration of pretreatment. KYAMC Journal Vol. 11, No.-2, July 2020, Page 83-86